LOCAL ECONOMIC DYNAMICS: OPPORTUNITIES AND CHALLENGES - Loso Judijanto; Lukman Hakim; Al-Amin (CV. Adiba Aisha Amira, 2024)
In the context of regional economic development, challenges and opportunities play a vital role in determining the direction of regional progress and growth. Obstacles include limited access to funding, inadequate infrastructure, competition with foreign products, and limited skilled human resources. These obstacles require serious attention from various parties such as the government, the private sector, and the community to find sustainable and effective solutions to overcome these problems. Key strategies include improving the quality of infrastructure, providing better access to funding, and improving education and training to support the development of skilled human resources. A focus on empowering Small and Medium Enterprises (SMEs), strengthening the competitiveness of local products, and innovation are crucial steps in creating a resilient regional economy. Cooperation between the government and the private sector in creating a conducive business environment is key to supporting sustainable economic growth. Amidst these obstacles, there are many opportunities that can be seized, especially by capitalizing on regional potentials such as unique natural and cultural resources. Development in sectors such as tourism and creative industries can be a key driver for regional economic growth. With the right strategy and strong cooperation between various stakeholders, the regional economy can grow rapidly and make a significant contribution to the welfare of the community, as well as becoming an important pillar for national economic development.